Analysis of Qualitative Studies of the Use of ICT in Learning Environments (European Journal of Teaching and Education, 2020)
This paper analyzes the qualitative methodological approaches used by the students of the Master’s Degree in Education during the years 2017, 2018 and 2019 from the Research Project entitled: Use of ICT in learning environments. For this analysis, it is reviewed the scope of research that incorporates the use of information and communication technologies in different educational contexts, in which students develop their research as a degree option to qualify for the Master’s Degree. It is also made a selection of the works that use the qualitative methodology in order to determine the designs and methods they use to achieve the objectives proposed in the Research. From this analysis, it is made a reading that allows to investigate new areas of study in the field of education, as well as other ways of approaching the use of ICT in a world where digital prevails and education is no stranger to these changes and evolution that is constantly taking place, which facilitates having recent data on the subject and the impact on the educational act.